Evaluating alternative compounds for strongyloidiasis therapy: Novel insights from larval migration inhibition test. - María Cambra-Pellejà; Elora Valderas-García; Rafael Balaña-Fouce; Jennifer de la Vega; Esther Del Olmo; Jennifer Antwi-Ekwuruke; Lara Linnemann; Lennart Heepmann; Minka Breloer; María Martínez-Valladares (PLoS Neglected Tropical Diseases)
Strongyloidiasis is a neglected tropical disease estimated to affect more than 600 million people worldwide. Recently, the World Health Organization road map on neglected tropical diseases 2021-2030 has put the focus on strongyloidiasis, including this disease within its mass drug administration campaigns. With the use of ivermectin in extensive treatment of all populations at-risk, identifying effective therapeutic alternatives is crucial in case ivermectin resistance arises. The objective of the present study was the development of a larval migration inhibition assay to evaluate the anthelmintic efficacy of commercial drugs and diamine and aminoalcohol derivatives against infective Strongyloides ratti third stage larvae. Through this technique, we successfully screened and estimated the in vitro anthelmintic efficacy of six commercial drugs, seven diamine derivatives and eight aminoalcohol derivatives. Unexpectedly, the half-maximal effective concentration of ivermectin and moxidectin (2.21 and 2.34 μM, respectively) were observed as the highest value obtained among all commercial drugs tested by this in vitro technique. Moreover, some diamine and aminoalcohol derivatives showed superior efficacy inhibiting S. ratti motility compared to ivermectin, with five compounds (AA23, AA34, AO2 AO7 and AO14b) also displaying selectivity indexes on HepG2 and Caco2 higher than 1. These findings underscore the potential of these derivatives as promising alternatives for strongyloidiasis treatment, warranting further investigation and in vivo efficacy assessment.